Empleo con apoyo y su relación con la inclusión laboral y social de los alumnos con discapacidad de la sección secundaria de la fundación El Triángulo en la ciudad de Quito. Año lectivo 2013- 2014 - Orbea Novillo, Jimena Jackeline (2015)
The content of this paper refers, in the first instance to the “EMPLOYMENT SUPPORT AND ITS RELATION WITH SOCIAL AND LABOR INCLUSION OF STUDENTS WITH DISABILITIES IN THE SECONDARY SECTIONOF THE CITY OF QUITO TRIANGLE FOUNDATION”; being the general objective: investigate the relationship between supported employment and labour Inclusion and Social of the students with disabilities of the secondary section of the El Triangulo Foundation. 2013-2014 school year. The methods used for the preparation of the present research work were: descriptive; It allowed to detail the current situation of the problem, ensuring its rational interpretation and analysis of the objective, analytical; became the critical study of the data obtained in field research, statistical; was used for the Organization and the graphics of the data obtained with the application of instruments of research, scientist; It is used to check the results and establish conclusions and recommendations. Techniques and instruments were: survey addressed to parents to determine employment and Social Inclusion in students with disabilities in the section secondary of the El Triangulo Foundation and the observation sheet addressed to teachers of students with disabilities in the section secondary of the El Triangulo Foundation to verify the practice of supported employment. In the results of the investigation, and after comparing empirical data with theoretical livelihoods, it was determined that: the supported employment allows 100% of youth with disabilities in the secondary section of the triangle Foundation, included work on the open market, allowing to start the process of autonomy. In terms of social inclusion was determined that 73% of youth with disabilities in the secondary section of the triangle Foundation have no equal as the rest of society because they have not undergone experiences in various environments like for example; family, school, community, to a large extent is due to overprotection of the parents, fear of being rejected by the society in any situation, perhaps by facilitating their daily lives and not rely on the capabilities of their children to interact with a different person. It was finally verified system employment support practice, where 100% of youth with disabilities in the secondary section of the triangle Foundation, are trained in a skill.